Human rights and humanitarian forensic action: the experience in Uruguay - Hugo Rodríguez Almada; Frances Borches Duhalde; Victoria Iglesias Salaverría (Forensic Sciences Research, 2022)
Humanitarian Forensic Action (HFA) is considered a new field of Forensic Medicine and Forensic Sciences where the forensic science is applied to different humanitarian activities. In Uruguay, the HFA has been developed based on international documents and developed some methodologies appropriate to the particular features of the country. The Department of Legal Medicine and Forensic Sciences has devised and maintained several lines of action in response to demands from public institutions and other requests from victims, families, prosecutors and courts. In every instance, humanitarian forensic work contributes to the education and training of young forensic professionals.